(untitled) (Innovative professional education, 2024)
The greening of the professional training of future specialists is conditioned by the need of society to implement the vectors of the sustainable development strategy; achieving their understanding of the essence of environmental problems based on the systematic, conscious and complete assimilation of the acquired knowledge; focusing the educational process on the acquisition of experience in environmental protection by future specialists; and the necessary factor – the formation of the readiness of a future specialist to take care of natural resources in the course of their work.